2022
DOI: 10.3390/app12146829
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Analysis of Oral Mucosa: An Observational Cross-Sectional Study

Abstract: (1) Background: Ultrasonography is gaining popularity as a diagnostic tool in the study of the oral mucosa. The precision of ultrasound has made it possible to identify the various layers, based on their echogenicity. The aim of this study was to perform a quantitative analysis of healthy oral mucosa based on the analysis of greyscale, echo levels (dB), and attenuation values (dB/cm). (2) Methods: Thirty-three patients (17 females and 16 males; 58.42 ± 13.29 y.o) were recruited for this study. The images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This finding corroborates the properties of HFUS in discriminating KM from alveolar mucosa based on the different reflection of the ultrasound waves. This observation is in line with previous studies in dentistry 20,21,24,33 and other medical fields 25,34 describing the ultrasonographic presentation of keratinized and nonkeratinized epithelia. The hyperechoic appearance of the keratinized epithelium compared to the alveolar mucosa is probably due not only to the presence of the keratin layer, but also to the superior thickness of the epithelium in KM compared to non-KM.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding corroborates the properties of HFUS in discriminating KM from alveolar mucosa based on the different reflection of the ultrasound waves. This observation is in line with previous studies in dentistry 20,21,24,33 and other medical fields 25,34 describing the ultrasonographic presentation of keratinized and nonkeratinized epithelia. The hyperechoic appearance of the keratinized epithelium compared to the alveolar mucosa is probably due not only to the presence of the keratin layer, but also to the superior thickness of the epithelium in KM compared to non-KM.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, KM width assessment with HFUS does not depend on the color of the soft tissue but rather on the acoustic impedance of the different anatomical structures. 24,37 Previous studies have shown the properties of this technology of assessing the position and thickness of the soft tissue and buccal bone, together with the outcomes of periodontal/peri-implant phenotype modifications. 12,18,19,30 The present study further demonstrated that HFUS can also be used to determine the width of KM at implant sites, that has been conventionally assessed with periodontal probes only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique for oral cavity exploration is not widely used, but various applications have been reported in the literature: ranging from the study of periodontal and peri-implant tissues to the clinical and surgical characterization of benign and malignant lesions of the oral mucosa [ 133 , 134 ]. Thanks to the advancement of technology, some recent ex vivo and in vivo studies suggest that high-frequency ultrasound holds the ability to distinguish between tissue layers based on image contrast [ 135 ]. This contrast represents the result of acoustic backscatter, which is directly proportional to the change in density found at the boundaries between tissue layers.…”
Section: Future Perspectivesmentioning
confidence: 99%